COMSOL Simulations of Density Fingering Instability in Channel: Characterizing Density Fingering Instability in Channel Flow (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Density fingering instability obtained when a more dense fluid lie on the less dense fluid and it is very fundamental importance in sequestration. In literature, various model are available for sequestration. process. Comparison and validity of various model were discussed. In this work, we perform the simulation in channel by taking unsteady Stoke's equation with forcing term. COMSOL multiphysics software is used to simulate the problem. Our results suggest that for low Atwood number, vertical centreline symmetry is obtained. Also, we show when Atwood number high, due to dominance of inertial force on viscous force, very chaotic instability is obtained.